Gender Discrimination in Management. Theoretical and Empirical Perspectives - Felicia Cornelia MACARIE; Octavian MOLDOVAN (Transylvanian Review of Administrative Sciences, 2012)
This paper reviews the permanently expanding literature on gender discrimination in management, focusing on women in decision making positions from both the public and private sphere. Different psychological mechanisms (such as stereotyping, attribution or equity), that are not necessarily mutually exclusive but rather complementary, determine individual manifestations in the form of discrimination (ranging from formal to informal, covert to overt and so on) against females. As a result, women are either underrepresented in top management (under normal conditions) or overrepresented in risky managerial positions (in periods of organizational crisis or downturn). Furthermore, even in the limited number of sectors where women represent more than half of the labor force (such as nursing, primary education or social services) men have better odds of being promoted, due to formal or informal assistance received from mentors of the same gender. Albeit rather incremental shifts toward a better representation of women in decision making positions can be observed in the last decades, both statistical and experimental data show that there is still a long way until their representation in managerial positions will reflect their involvement in the workforce.